The effects of focus versus diversification on bank performance: Evidence from Chinese banks - Allen N. Berger; Iftekhar Hasan; Mingming Zhou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This paper investigates the effects of focus versus diversification on bank performance using data on Chinese banks during the 1996-2006 period. We construct a new measure, economies of diversi-fication, and compare the results to those of the more conventional focus indices, which are based on the sum of squares of shares in different products or regions. Diversification is captured in four dimensions: loans, deposits, assets, and geography. We find that all four dimensions of diversifica-tion are associated with reduced profits and higher costs. These results are robust regardless of al-ternative measures of diversification and performance. Furthermore, we observe that banks with foreign ownership (both majority and minority ownership) and banks with conglomerate affiliation are associated with fewer diseconomies of diversification, suggesting that foreign ownership and conglomerate affiliation play an important mitigating role. This analysis may provide important implications for bank managers and regulators in China as well as in other emerging economies.
URN:NBN:fi:bof-201408072010
Keywords: G21; G28; G34; 330; Diversification; focus; efficiency; Chinese banking